2023
DOI: 10.7554/elife.87860
|View full text |Cite
|
Sign up to set email alerts
|

The yeast RNA methylation complex consists of conserved yet reconfigured components with m6A-dependent and independent roles

Abstract: N6-methyladenosine (m6A), the most abundant mRNA modification, is deposited in mammals/insects/plants by m6A methyltransferase complexes (MTC) comprising a catalytic subunit and at least five additional proteins. The yeast MTC is critical for meiosis and was known to comprise three proteins, of which two were conserved. We uncover three novel MTC components (Kar4/Ygl036w-Vir1/Dyn2). All MTC subunits, except for Dyn2, are essential for m6A deposition and have corresponding mammalian MTC orthologs. Unlike the ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 86 publications
1
16
0
Order By: Relevance
“…An earlier study showed that disruption of SLZ1 decreased m6A by 80% (Agarwala et al, 2012). However, a recent study reported that no m6A levels were detected across different phases of early meiosis in slz1Δ cells (Ensinck et al, 2023). It is worth noting that slz1Δ cells also display a mild meiotic phenotype comparable to that of IME4 CD .…”
Section: The Yeast Mtc Is Conserved With Distinct Featuresmentioning
confidence: 92%
See 4 more Smart Citations
“…An earlier study showed that disruption of SLZ1 decreased m6A by 80% (Agarwala et al, 2012). However, a recent study reported that no m6A levels were detected across different phases of early meiosis in slz1Δ cells (Ensinck et al, 2023). It is worth noting that slz1Δ cells also display a mild meiotic phenotype comparable to that of IME4 CD .…”
Section: The Yeast Mtc Is Conserved With Distinct Featuresmentioning
confidence: 92%
“…However, in other common lab strain backgrounds, for example, S288C and Σ1278b, IME4 is required for meiosis and spore formation (Clancy, 2002;Hongay et al, 2006;Shah et al, 1992). Cells that harbour the catalytically inactive Ime4 (IME4 CD ) display a much milder meiotic phenotype indicating that Ime4 possesses an important noncatalytic function in meiosis (Agarwala et al, 2012;Bushkin et al, 2019;Ensinck et al, 2023;. Two additional proteins, Mum2 and Slz1, were identified to interact with Ime4.…”
Section: The Yeast Mtc Is Conserved With Distinct Featuresmentioning
confidence: 99%
See 3 more Smart Citations

mRNA m6A detection

Moshitch-Moshkovitz,
Sevilla-Sharon,
Ashwal-Fluss
et al. 2024
Nat Rev Methods Primers